Below or all the way to the peak? Oxygen uptake efficiency slope as the index of cardiorespiratory response to exercise—the NOODLE study - Kasiak, Przemysław; Kowalski, Tomasz; Rębiś, Kinga; Klusiewicz, Andrzej; Starczewski, Michał; Ładyga, Maria; Wiecha, Szczepan; Barylski, Marcin; Poliwczak, Adam Rafał; Wierzbiński, Piotr; Mamcarz, Artur; Śliż, Daniel (Frontiers in physiology, 2024)
Background: The ratio of oxygen uptake (VO 2 ) to minute ventilation (VE) is described as the oxygen uptake efficiency slope (OUES). OUES has been suggested as a valuable submaximal cardiorespiratory index; however, its characteristics in endurance athletes remain unknown. In this study, we a) investigated OUES between different time intervals, b) assessed their prediction power for VO 2 peak, and c) derived new prediction equations for OUES tailored for well-trained individuals. Materials and Methods: A total of 77 male (age = 21.4 ± 4.8 yrs; BMI = 22.1 ± 1.6 kg·m −2 ; peak oxygen uptake = 4.40 ± 0.64 L·min −1 ) and 63 female individuals (age = 23.4 ± 4.3 yrs; BMI = 23.1 ± 1.6 kg·m −2 ; peak oxygen uptake = 3.21 ± 0.48 L·min −1 ) underwent the cycling cardiopulmonary exercise test. OUES was measured at 75%, 90%, and 100% of exercise duration. Prediction power and new models were derived with the multiple linear regression method. Results: In male subjects, OUES [mL·min −1 /L·min −1 ] from 75% = 4.53 ± 0.90, from 90% = 4.52 ± 0.91, and from 100% = 4.41 ± 0.87. In female subjects, OUES [mL·min −1 /L·min −1 ] from 75% = 3.50 ± 0.65, from 90% = 3.49 ± 0.62, and from 100% = 3.41 ± 0.58. OUES did not differ between time intervals in male ( p = 0.65) and female individuals ( p = 0.69). OUES strongly predicts peak VO 2 independently from the measuring interval ( β = 0.71–0.80; R 2 = 0.50–0.63). The prediction model designed for elite athletes was OUES [mL·min −1 /L·min −1 ] = −1.54 + 2.99; BSA [m 2 ]—0.0014; (age [in years]; sex [1 = male, 2 = female]) ( R 2 = 0.36). Conclusion: OUES enables an accurate prediction of peak cardiorespiratory fitness in elite endurance athletes. OUES is a feasible alternative to maximal exercise testing. A new prediction equation should be used for highly trained individuals. Physicians should understand OUES physiology to properly assess the cardiorespiratory response to exercise in athletic cohorts.